Kedokteran Sebagai Ilmu Pandangan Kedokteran Sekarang Teerhadap dirinya - T. Jacob T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
The author defines medicine as efforts to understand, maintain and manage health condition of human beings, as individuals as well as members of a society, in a biosocial matrix. Thus, three sets of disciplines are involved, i. e. the basic medical sciences, the clinical medical sciences and the social medical sciences.Besides, four aspects of medicine should be taken into consideration, namely medicine as science, technology, art and craft. Also, attention should be paid to the fact that diseases and medical interventions could occur at any level of the I :ing system, each having its own charac• teristics, and with emergents appearing in cross:level surveys.The unavoidable subspecialization in modern medicine should be balanced by transdisciplinary communication and interdisciplinary efforts, and by holistic approach to health problems utilizing the biosociomedical concept of health. Four tracts of study are suggested in medical education, i. e. population medicine, surgical sciences, medical sciences, and basic medical sciences.In conjunction with these steps early compartmentalization in the senior high school curriculum should be avoided.Key Word:: medical education - scientific medicine - living systems - concepts of disease - medical specialization